Cancellation of Article 55 of The Public Accountant Law by The Constitutional Court Decision - Fikri, Herman (Jurnal Dinamika Hukum, 2023)
The Public Accountant profession could be punished without a Constitutional Court Decision. Because it can be punished, the Public Accountant Professional Association filed a lawsuit with the Constitutional Court with rational reasons that form the basis of the petition. The research conducted is normative legal research. The results of the study state that Public Accountants are in a subordinate and minor position due to the lack of protection for the exercise of their profession, given the high legal threat. Even if it is true that the intent of the formulation of Article 55 Letter a of the Public Accountants Law is to protect the public interest from the possibility of falsification or fraud perpetrated by an Accountant, the public's interests have been adequately protected by the provisions of the Criminal Code (delict of counterfeiting or fraud), so, therefore, the provisions of Article 55 letter a The law is an exaggerated and even fantastic provision. Thus, Article 55 letter a of the law creates uncertainty in the law and contradicts the principle of lex certa, which is the basic principle in criminal law of the inclusion of criminal sanctions as determined by Articles 55 and Article 56 of the law in the perspective of humanistic criminal law is imprecise and irrational. So, it is essential to regulate the accounting profession, which should be the basic idea of strengthening the profession, which is used as a standard or orientation point of view, reduced by the criminalization in Article 55 letter b, which creates fear in the world of accountants.